A social innovation approach to programming to address social issues. Issue 3 (27th May 2022) - Hill, John C.; Hains, Kristina; Hains, Bryan; Hustedde, Ronald
ABSTRACT: Social innovation can be defined as a more effective solution to a social problem that positively impacts society. The following manuscript is a conceptual discussion where the authors propose a five-stage approach to utilizing social innovation in designing and implementing innovative programming to address complex social issues. The authors provide a unique example that applies this process as the foundation, within a unique musical context. Ultimately, it is hoped by utilizing social innovation concepts within the programming foundation, it will lead to alternative perspectives when addressing complex social issues.